The improvement of suspension training for trunk muscle power in Sanda athletes - Xiujie Ma; Wei Sun; An Lu; Pei Ma; Chuanyin Jiang (Journal of Exercise Science & Fitness, 2017)
The aim of this study was to investigate whether both suspension training (ST) and traditional training (TT) can improve Sanda athlete's strength quality of trunk muscles and to explore the effect of suspension training on Sanda athletes' trunk muscle power production. Twelve elite Sanda athletes from the Competitive Sports School of Shanghai University of Sport were randomly assigned to experimental group (EG) and control group (CG). EG and CG were regularly trained with suspension training and traditional strength training for 40 minutes three times per week. The total duration of training was 10 weeks. The measurements including peak torque (PT), PT/body weight (BW), and rate of force development (RFD) were used to assess trunk muscles strength. The results showed that there were significant differences between the two groups' performance when it was tested at the higher velocity of dynamometer (test of muscle power), but less significant differences when the two groups performance was tested at the lower velocity of dynamometer (test of maximum strength). The conclusion of this study is that compared with traditional training methods, suspension training can improve back and trunk flexion muscles strength more effectively. In particular, suspension training can improve the explosive power of trunk extension and flexion muscles.